2005
DOI: 10.1007/s00520-005-0806-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of progressive muscle relaxation training and guided imagery in reducing chemotherapy side effects in patients with breast cancer and in improving their quality of life

Abstract: These results indicate that PMRT and GI were associated with both the improvements in ANV and PNV and in the QoL of patients with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
13

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 32 publications
3
76
0
13
Order By: Relevance
“…Though age is regularly ascribed as an effect on anxiety during cancer treatment (Cohen, 2014;Jacobsen et al, 1993), this was not the case in the current sample although a wide age range was covered. We found that rather physical symptoms experienced while undergoing chemotherapy influence a persons' general vulnerability to react anxiously (state anxiety), explaining why interventions that address chemotherapy side-effects are also effective in reducing anxiety (Vasterling et al, 1993;Yoo et al, 2005). However, when symptom burden and trait anxiety were regressed together on state anxiety levels, the situational anxiogenic effects of symptom burden disappeared.…”
Section: Discussionmentioning
confidence: 81%
“…Though age is regularly ascribed as an effect on anxiety during cancer treatment (Cohen, 2014;Jacobsen et al, 1993), this was not the case in the current sample although a wide age range was covered. We found that rather physical symptoms experienced while undergoing chemotherapy influence a persons' general vulnerability to react anxiously (state anxiety), explaining why interventions that address chemotherapy side-effects are also effective in reducing anxiety (Vasterling et al, 1993;Yoo et al, 2005). However, when symptom burden and trait anxiety were regressed together on state anxiety levels, the situational anxiogenic effects of symptom burden disappeared.…”
Section: Discussionmentioning
confidence: 81%
“…Studies carried out in different fields (stoma patients, patients receiving chemotherapy, dialysis and psychiatric patients, etc) have proved progressive relaxation exercises to be effective in reducing anxiety (9,(16)(17)(18)(19)(20)(21)(38)(39)(40)(41)(42)(43). Dehdari et al (44) applied to patients after CABG surgery studies of state and permanent PMR by reducing levels of anxiety reported that improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Because surveys vary in terms of definitions of CAM and of specific types of therapy included in questionnaires, the assessment of overall prevalence is somewhat complicated. Noninvasive therapies like acupuncture, chiropractic, massage, spiritual healing, meditation, and imagery are most common, but use of dietary supplements is rapidly gaining terrain [4][5][6][7][8]. As a result, the economic impact of CAM is enormous.…”
Section: Worldwide Use Of Cammentioning
confidence: 99%